Comparison of Oral versus Intravenous Proton Pump Inhibitors in Preventing Re-bleeding from Peptic Ulcer after Successful Endoscopic Therapy - Ibrahim Moklad Alrogi, Adel Adam Altowaleei, Abdullah Hamdan Alsefri, Abdulaziz Shalah Alotaibi, Nareman Khalid Andijani, Majed Hasan Alammari, Ali Hosin Aamri, Abdulelah Mohammed Saeed Alghamdi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Peptic ulcer disease (PUD) consider a complex condition that can arise from a range of etiological factors. These include elevated dietary patterns, psychological strain, gastric acid secretion, Helicobacter pylori (H. pylori) infection, & prolonged administration of nonsteroidal anti-inflammatory medications. Bleeding, obstruction, & perforation continue to be the most encountered complications of PUD.Objectives: To assess the efficacy of intravenous versus oral PPI in blocking rebleeding from peptic ulcers after successful endoscopic treatment.Methods: The randomized controlled trials' inclusion criteria were to include: (i) each and every case who presented to the hospital with signs of ulcer bleeding, as demonstrated by haematemesis or melaena; (ii) an endoscopic procedure was carried out in order to halt the bleeding; (iii) patients were randomly assigned to receive PPIs either orally or intravenously; & (iv) a minimum of one of the subsequent outcomes—recurrent bleeding, surgical intervention, or mortality—was documented after the endoscopy procedure. Excluded were clinical trials that investigated cases involving malignant hemorrhage or patients who were already undergoing therapy with PPIs.Results: throughout a one-month monitoring period, the involved research found no statistically significant variations among both groups Oral-Pan & IV-Pan) regarding the rates of re-endoscopy & re-bleeding, period of stay in hospital, operation, volume of blood transfusion, & mortality. Similar findings have been reported in several additional investigations. Conclusion: The findings of our research indicate that cases with bleeding peptic ulcers and an elevated risk of re-bleeding may benefit from high-dose oral PPIs as an alternative to high-dose IV PPIs. The increased cost & accessibility of oral PPIs contribute to their considerably reduced cost.